2020
DOI: 10.1080/1540496x.2020.1791074
|View full text |Cite
|
Sign up to set email alerts
|

How Does COVID-19 Affect China’s Insurance Market?

Abstract: The insurance market has been greatly impacted by the outbreak of the COVID-19 pandemic. We employ monthly provincial panel data and fixed-effects models to study how COVID-19 has impacted China's insurance market. The study finds that the commercial insurance premium income, the monthly year-onyear growth rate of premium, insurance density, and insurance depth have all decreased due to COVID-19. The negative impacts on property and personal insurances are both statistically significant. Raising the level of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(61 citation statements)
references
References 14 publications
2
48
0
2
Order By: Relevance
“…Following Wang et al. [29] , we also calculate the logarithm of the cumulative number of COVID-19 confirmed cases in each province (lnCOVID) and the cumulative number of COVID-19 confirmed cases divided by the number of permanent residents in each province (PCCOVID) as the core independent variables for measuring COVID-19. Table 1 summarizes the definitions of variables in the model.…”
Section: Modelmentioning
confidence: 99%
“…Following Wang et al. [29] , we also calculate the logarithm of the cumulative number of COVID-19 confirmed cases in each province (lnCOVID) and the cumulative number of COVID-19 confirmed cases divided by the number of permanent residents in each province (PCCOVID) as the core independent variables for measuring COVID-19. Table 1 summarizes the definitions of variables in the model.…”
Section: Modelmentioning
confidence: 99%
“…In other words, we examine whether market volatility at the Asian regional level can explain stock market volatility at the country-level. Recent studies have shown that the COVID-19 pandemic has significantly affected global economies; see, for instance, Mishra et al (2020), Salisu & Akanni (2020), Chen et al (2020), Wang et al (2020), Yue et al (2020), Yu et al (2020), Xiong et al (2020), Shen et al (2020), Gu et al (2020), Haroon & Rizvi (2020), Iyke (2020), He et al (2020), and Liu et al (2020). According to Sha & Sharma (2020) and Phan & Narayan (2020), the COVID-19 pandemic represents the largest and most disturbing shock to the global economic system and it is therefore important to understand whether the country level volatility can be determined by the regional level stock market volatility.…”
Section: Introduction I Introductionmentioning
confidence: 99%
“…A growing body of literature demonstrates that the COVID-19 pandemic affected different facets of economies (Sha & Sharma, 2020). This literature can be distilled along several lines, including those showing that the pandemic impacted: corporate outcomes, such as liquidity and cashholdings (Fu & Shen, 2020); stock markets (Haroon & Rizvi, 2020;Salisu & Sikiru, 2020); oil markets (Devpura & Narayan, 2020;Iyke, 2020a;Narayan, 2020a;; foreign exchange markets (Iyke, 2020b;Narayan, 2020b); global trade and insurance markets (Vidya & Prabheesh, 2020;Wang et al, 2020); and global politics (Apergis & Apergis, 2020), among others.…”
Section: Introduction I Introductionmentioning
confidence: 99%